Spatiotemporal analysis of solar ultraviolet radiation based on Ozone Monitoring Instrument dataset in Iran, 2005–2019. (15th October 2021) - Gholamnia, Reza; Abtahi, Mehrnoosh; Dobaradaran, Sina; Koolivand, Ali; Jorfi, Sahand; Khaloo, Shokooh Sadat; Bagheri, Amin; Vaziri, Mohammad Hossein; Atabaki, Yasamin; Alhouei, Farnaz; Saeedi, Reza
Abstract: The solar ultraviolet radiation (UVR) at national, provincial and county levels in Iran during 2005–2019 were determined based on Ozone Monitoring Instrument (OMI) dataset. The temporal (annual and monthly) trends and spatial distributions of the UVR in terms of erythemally weighted daily dose (EDD), erythemally weighted irradiance at local solar noon time (EDR), and UV index and the major factors influencing the spatiotemporal trends were analyzed. The population-weighted average values of EDD, EDR, and UV index in Iran were respectively 3631 J/m 2, 176.3 mW/m 2, 7.1 in 2005 and rose by 0.22% per year to 3744 J/m 2, 181.7 mW/m 2, and 7.3, respectively in 2019, but the annual trend was not statistically significant. The EDD in Iran during the study period exhibited the highest monthly average value in June (6339 J/m 2 ) and the lowest one in December (1263 J/m 2 ). The solar UVA/UVB ratios at the national level during 2005–2019 were considerably lower in summer. The EDD provincial average values in the study period were in the range of 2717 (Gilan) to 4424 J/m 2 (Fars). The spatiotemporal variations of the solar UVR parameters were well described by the linear models as a function of cloud optical thickness (COT), ozone column amount, surface albedo, latitude, and altitude (R 2  > 0.961, p value < 0.001) and the temporal changes of the solar UVR parameters were mainly caused by the COT. The results indicated that non-burning exposure to solar UVR in summer can be more efficient for vitamin D synthesis due to higher contribution of UVB in the solar UVR. The spatial distributions and temporal trends should be considered to determine the optimal duration, time and condition of exposure to the solar UVR for the public and occupational training and public health measures. Graphical abstract: Temporal trend and spatial distribution of population-weighted average values of the EDD in Iran during 2005–2019. Image 1 Highlights: The solar ultraviolet radiation (UVR) in Iran during 2005–2019 were determined. The population-weighted averages of EDD, EDR, and UV index in Iran rose by 0.22% per year. The annual changes of the solar UVR parameters were mainly caused by the COT. The highest and lowest monthly averages of the EDD occurred in June and December, respectively. The EDD provincial averages were in the range of 2717 (Gilan) to 4424 J/m 2 (Fars).